2023
DOI: 10.1080/02670836.2022.2110339
|View full text |Cite
|
Sign up to set email alerts
|

Strain rate sensitivity and toughness behaviour of ductile iron under specific loading

Abstract: An efficient assessment of the mechanical properties of ductile iron (DI) under dynamic loading is usually missing. To address this gap, a plasticity model for DI grade EN-GJS-500-14 was suggested. Fracture mechanics (FM) and Charpy impact (CI) tests, high-speed and impact tensile tests as well as tensile tests at variable temperature and stress states were carried out on DIs with silicon contents from 2.10 to 3.64 wt-%. Toughness-related results indicate a difference in the transition temperatures of 100–140 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…There are four common failure modes of metal materials, which are cleavage fracture, ductile fracture, intergranular fracture, and fatigue [4,5]. The mechanical properties and fracture mechanism of ductile iron at different conditions have mainly been investigated [6][7][8][9][10][11][12]. In the in situ experiment, Di Cocco [13] observed the surface of tensile specimen by scanning electron microscope, and found that the main damage mechanism of FDI is the nucleation and propagation of graphite nodule cracks caused by the decrease of solubility of γ phase carbon ('Onion-like' mechanism).…”
Section: Introductionmentioning
confidence: 99%
“…There are four common failure modes of metal materials, which are cleavage fracture, ductile fracture, intergranular fracture, and fatigue [4,5]. The mechanical properties and fracture mechanism of ductile iron at different conditions have mainly been investigated [6][7][8][9][10][11][12]. In the in situ experiment, Di Cocco [13] observed the surface of tensile specimen by scanning electron microscope, and found that the main damage mechanism of FDI is the nucleation and propagation of graphite nodule cracks caused by the decrease of solubility of γ phase carbon ('Onion-like' mechanism).…”
Section: Introductionmentioning
confidence: 99%